Recent advances in non-noble metal electrocatalysts for nitrate reduction - Zhang, Xi; Wang, Yuting; Liu, Cuibo; Yu, Yifu; Lu, Siyu; Zhang, Bin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
[Display omitted] •Non-noble metal electrocatalysts for nitrate reduction are reviewed.•Mechanisms of nitrate electroreduction are discussed.•Strategies to improve electrochemical performance are presented.•Challenges and outlooks of non-noble metal electrocatalysts for nitrate reduction are given. Nitrate pollution has become a serious global problem, threatening human health and ecosystems. The electrochemical reduction has emerged as an energy-efficient and environmental-friendly technology to remove nitrate from water. Recently, non-noble metal electrocatalysts have attracted increasing attention in nitrate reduction due to their great advantages in terms of low cost, high activity, and large-scale application potential. This review highlights the latest research progress in the area of non-noble metal materials for electrochemical nitrate reduction. The mechanistic insight into the electrochemical reduction of nitrate is briefly discussed. Meanwhile, numerous examples in this field are collected and analyzed. Some strategies employed to improve the performance of nitrate electroreduction are also presented. Finally, the challenges and prospects in this field are discussed. This review hopes to guide the design and development of efficient non-noble metal electrocatalysts for nitrate reduction on a large scale.